On the dynamics of a high-order Lorenz-Stenflo system - Rech P.C.* (2016)
© 2016 The Royal Swedish Academy of Sciences.Results presented in a recent paper in this journal concerning a continuous-time dynamical system, namely that involving high-order Lorenz-Stenflo equations, are extended in this paper. More specifically, the present paper reports on nonlinear dynamics of a six-variable, four-parameter high-order Lorenz-Stenflo system. Six cross-sections of a four-dimensional parameter-space are considered. By using Lyapunov exponents spectra to characterize the dynamical behavior at each point of each of these plots, it is shown that different regions are allowed, from equilibrium point to chaos regions. It is also shown that hyperchaos is not an allowed behavior in a high-order Lorenz-Stenflo system. In addition, new results reported here are compared with those obtained for the original Lorenz-Stenflo system.